2017
DOI: 10.1111/jre.12456
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable gelatin/beta‐tricalcium phosphate sponges incorporating recombinant human fibroblast growth factor‐2 for treatment of recession‐type defects: A split‐mouth study in dogs

Abstract: Within the limitations of this study, rhFGF-2 in gelatin/β-TCP sponges exhibits an increased potential to support periodontal wound healing/regeneration in canine recession-type defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Therefore, it can be speculated that a scaffold provides better stability to the blood clot and GF. Consistent with these findings, two recent preclinical studies showed superior outcomes when FGF‐2 was incorporated into the scaffolds compared with FGF‐2 alone . Enhanced new cementum and bone was observed in the site treated with FGF‐2 and a biodegradable sponge, while another group found that a collagen matrix scaffold was able to enhance the amount of root coverage using FGF‐2 at 4 and 16 weeks .…”
Section: Fibroblast Growth Factor‐2supporting
confidence: 53%
See 3 more Smart Citations
“…Therefore, it can be speculated that a scaffold provides better stability to the blood clot and GF. Consistent with these findings, two recent preclinical studies showed superior outcomes when FGF‐2 was incorporated into the scaffolds compared with FGF‐2 alone . Enhanced new cementum and bone was observed in the site treated with FGF‐2 and a biodegradable sponge, while another group found that a collagen matrix scaffold was able to enhance the amount of root coverage using FGF‐2 at 4 and 16 weeks .…”
Section: Fibroblast Growth Factor‐2supporting
confidence: 53%
“…Fibroblast growth factor‐2 (FGF‐2) is a heparin‐biding cytokine which is able to enhance the angiogenic and osteogenic activity of multiple cellular populations . In addition, FGF‐2 can stimulate the proliferation and migration of mesenchymal cells within the PDL .…”
Section: Fibroblast Growth Factor‐2mentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies showed that acidic gelatin sponge (IEP 5.0) had a high affinity to rhFGF‐2, which is basic in vivo, and formed gelatin complexes ionically . The effect of controlled rhFGF‐2 release can be achieved by gelatin decomposition to enhance hard and soft tissue regeneration in in vivo studies . On the contrary, in vitro studies have reported that basic gelatin sponges (IEP 9.0) rarely have an affinity to rhFGF‐2 and do not exhibit polyion complexation.…”
Section: Discussionmentioning
confidence: 99%